IDEOLOGICAL TRAP IN EDUCATION: Rivalry Discourse on Islamic Literatures in NW and Salafi Schools in Lombok - Saparudin Saparudin (TARBIYA: Journal of Education in Muslim Society, 2022)
This study aimed to analyze the ideological contestation between the Nahdlatul Wathan (NW) as a local Islamic group and Salafis as a transnational Islamic group in the Islamic literature, which is utilized as teaching materials in NW and Salafi schools. The rivalry between these two religious groups become a novel phenomenon in Lombok together with the increasing influence of the Salafi group. The success of Salafis in promoting the manhaj salaf, which in many ways contradicts the Aswaja promoted by NW in Islamic practice, has implications for the strengthening of the ideological content in Islamic textbooks in their respective schools. Based on the identification of literature books utilized as teaching materials, as analyzed based on the contestation theory by Antje Wiener and apparatuses of ideology theory by Louis Althusser, this study argues that religious literature used as teaching materials in Islamic schools is an instrument of ideological trapping of religious groups to generate apparatuses of ideology to win the contestation. The teaching materials contain negation of one another, mono-interpretation, and misleading one another. Finally, students only accept particular religious understandings indoctrination without being taught to think critically regarding different religious perspectives. In this context, a state polyce is needed to makesure that the higher order thinking skills of students have been developing, rather than ideological traping of certain Islamic group.